The effect of commuting cost to employment centers on urban property values : a spatial analysis in Bogotá, Colombia (2015)
We study the effect that changes of commuting costs to intra urban employment centers may have on property prices in Bogotá, Colombia. To explore the relationship between prices and communing costs, we use a difference in difference spatial model. Parametric and non-parametric estimations suggest a negative and significant impact of commuting costs on property values for dwellings far away from employment centers. The estimated price elasticity with respect to commuting costs for housing located in distant zones, indicates that a 1% increase in fuel price, reduces property values in 1.48%. Nonparametric Geographically Weighted Regression (GWR) showed to outperform traditional Spatial Autoregressive (SAR, SEM) models.